2014
DOI: 10.1016/j.jctb.2013.11.001
|View full text |Cite
|
Sign up to set email alerts
|

Triangle-free intersection graphs of line segments with large chromatic number

Abstract: In the 1970s, Erdős asked whether the chromatic number of intersection graphs of line segments in the plane is bounded by a function of their clique number. We show the answer is no. Specifically, for each positive integer k, we construct a triangle-free family of line segments in the plane with chromatic number greater than k. Our construction disproves a conjecture of Scott that graphs excluding induced subdivisions of any fixed graph have chromatic number bounded by a function of their clique number. arXiv:… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
104
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 88 publications
(105 citation statements)
references
References 12 publications
1
104
0
Order By: Relevance
“…Recently [12], we showed that the answer is negative. Namely, for every positive integer k we construct a family F of line segments in the plane with no three pairwise intersecting segments and such that χ(F) > k.…”
Section: It Is Clear That χ(G) ω(G)mentioning
confidence: 99%
See 1 more Smart Citation
“…Recently [12], we showed that the answer is negative. Namely, for every positive integer k we construct a family F of line segments in the plane with no three pairwise intersecting segments and such that χ(F) > k.…”
Section: It Is Clear That χ(G) ω(G)mentioning
confidence: 99%
“…We already posed several problems concerning the chromatic number and independence number of triangle-free segment intersection graphs in [12]. Here we focus on classification of shapes with respect to whether triangle-free families of copies of the shape under particular transformations have bounded or unbounded chromatic number.…”
Section: Open Problemsmentioning
confidence: 99%
“…It is also shown in [7] how the graph G k is represented as a segment intersection graph. I will show that there is an assignment w k of positive integer weights to the vertices of G k with the following properties:…”
Section: Constructionmentioning
confidence: 99%
“…Pawlik et al [7] define also a graphG k , which arises from (G k , P k ) by adding, for every probe P ∈ P k , a diagonal d P connected to all vertices in P. This is the smallest triangle-free segment intersection graph known to have chromatic number greater than k. Define the assignmentw k of weights to the vertices ofG k so thatw k is equal to w k on the vertices of G k andw k (d P ) = 1 for every P ∈ P k . Let I be an independent set inG k .…”
Section: Improved Constructionmentioning
confidence: 99%
“…The corresponding edges form a planar subgraph of G, therefore we would obtain |E(G)|/c k ≤ 3n − 6, where n ≥ 3 denotes the number of vertices of G. This would imply |E(G)| = O k (n), as required. However, Pawlik, Kozik, Krawczyk, Lasoń, Miczek, Trotter, and Walczak [PawK12] constructed systems of n segments, no 3 of which are pairwise intersecting, such that they cannot be decomposed into fewer than log log n subsystems of disjoint segments. Therefore, the answer to Erdős' question is no.…”
Section: Relaxations Of Planaritymentioning
confidence: 99%